Diaspora, memory and identity : a search for home - Agnew, Vijay, 1946- (Canadian social history series A fatherly eye, 2005)
Diaspora, Memory, and Identity is an exciting and innovative collection of essays that examines the nuanced development of theories of Diaspora, subjectivity, double-consciousness, gender and class experiences, and the nature of home.